TUNNEL VENTILATION AND HEAT-LOAD SURVEY BYRD STATION, ANTARCTICA, 1965. - Hoffman, C. R. (1966)
A ventilation and heat-load survey was conducted in the undersnow tunnels at Byrd Station, Antarctica, in late December 1965. This work was performed to obtain current information on tunnel cooling requirements and to obtain data for tunnel cooling system design. The survey showed that average tunnel temperatures are 5 to 6F lower than during a similar survey conducted in 1963, but are still as much as 18F higher than the desired temperature of 0F. Doors originally installed at tunnel entrances have deformed and become inoperative, allowing the free circulation of warm surface air throughout the undersnow camp. It was concluded that tunnel temperatures in the undersnow camp can be reduced by installation of airtight bulkheads and suitable selfclosing doors to prevent the inflow of warm, surface air and reduce cross-circulation between tunnels. All tunnels except L-7, which contains the communications galley and generator buildings, can be adequately cooled by drawing cold air from tunnel walls. A cooling system based on the U. S. Naval Facilities Engineering Command's air-plenum concept appears to be the most suitable means of cooling tunnel L-7. (Author)